The 2012 11th International Conference on Optical Communications and Networks (ICOCN) 2012
DOI: 10.1109/icocn.2012.6486244
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bandpass bandwidth in bit-rate and distance of subcarrier multiplexing on multimode fiber

Abstract: Transmitting a high data rate signal (> 1 Gbps) over multimode fiber can be done successfully if the high frequency range of multimode fiber is utilized. With this high frequency range, the available data rate can be increased significantly comparing to the achievable rate from the 3-dB intermodal bandwidth. However, there two major problems of transmitting signals over this high frequency of multimode fiber; that is, the attenuation and the deep nulls in its frequency response. To successfully exploiting this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Normally, this application is used for small distance, data of audio and video applications in LANs. The research identified that bandwidth and data rate increased but the maximum distance is covered and reduced for multimode fiber [24]. Beside, multimode fiber also is used as a high-resolution, lossless spectrometer [25].…”
Section: Optical Fibers Characteristicmentioning
confidence: 99%
“…Normally, this application is used for small distance, data of audio and video applications in LANs. The research identified that bandwidth and data rate increased but the maximum distance is covered and reduced for multimode fiber [24]. Beside, multimode fiber also is used as a high-resolution, lossless spectrometer [25].…”
Section: Optical Fibers Characteristicmentioning
confidence: 99%